Thermodynamics. - Fermi, Enrico, 1901-1954 (Dover Books on Physics and Mathematical Phisics, 1956)
These lectures by Enrico Fermi make great reading for undergraduates in chemistry or physics, particularly those undergoing the rigors of physical chemistry and chemical thermodynamics. Fermi writes with clarity, always carefully laying the appropriate groundwork for each topic. The mathematics assumes familiarity with calculus, including partial differentiation. Fermi provides clear explanations and motivation for the mathematics and the derivations are complete and easy to follow. For example, he carefully explained the form of a perfect differential of two variables and how it can be more readily integrated. I appreciated this help. The first four chapters will be familiar to students of physics: Thermodynamic Systems, First Law of Thermodynamics, Second Law of Thermodynamics, and Entropy. The derivation of the Clapeyron equation and the Van der Waals equation may be new to some students. Thereafter, the text begins to look more like physical chemistry with chapters titled Thermodynamic Potentials, Gaseous Reactions, Thermodynamics of Dilute Solutions, and the Entropy Constant. I found these last chapters to be more difficult, but not overly so. At some points Thermodynamics becomes a real page-turner, but not in the sense of a fast-paced action story. The page-turning is necessary to retrieve earlier mathematical expressions. Occasionally, you will encounter statements like "the expression for the free energy is immediately obtained from equations (111), (29), and (86)." Fermi does not allow the reader to forget earlier derivations and discussions. If your familiarity with thermodynamics is limited (or now foggy due to the passage of years), I suggest first reading Understanding Thermodynamics by H. C. Van Ness. This 100-page book, a series of lectures, is an excellent introduction to thermodynamics from an engineering and physics perspective. It corresponds to the first four chapters of Fermi's text.